PENGARUH SITOTOKSIK EKSTRAK BUAH MAHKOTADEWA [Phaleria macrocarpa (Scheff) Boerl.] TERHADAP SEL KANKER LESTARI HeLA - Pertamawati, Pertamawati (Badan Pengkajian dan Penerapan Teknologi, 2007)
Fruits of mahkotadewa (Phaleria macrocarpa (Scheff) Boerl). has been used to cure various health problems, including empirical treatment for cancer. The therapeutic effect of natural material is related to the chemical compounds it contain. In fruits of Phaleria macrocarpa, various chemicals are present such as flavonoid and tannin, both show anticancer activity, as well as other unknown ones presumably supportive for cancer treatment. An in vitro experiment is therefore set up with the objective of examining the effect of fruit extract on human uterine cervical carcinoma cells (HeLa cells). Various concentrations: 5, 10, 25, 50 and 100 ppm of fruit extract were evaluated. Observations were made 24, 72 and 120 hour after incubating HeLa cells in each treatments. The results showed that fruit might inhibit the growth of HeLa cells. Inhibitory concentration (IC50) of fruit extract after 24 hours of incubation is 6,21 ppm, after 72 hour of incubation is 5,09 ppm dan 5,73 ppm for 120 hour of incubation. Inhibitory potential of fruits in 72 hour of incubation is a highest ones. The effect might be associated to the active compounds contained in these material.